The strategy bridge theory for practice - Gray, Colin S. (Oxford : Oxford University Press, 2010)
'The Strategy Bridge' presents and explains the general theory of strategy and demonstrates the relevance of that theory to the real world of practice. The author explains what strategy is and how it relates to politics and warfare.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 6, 2010).
Keywords: Strategy